Research into effectiveness of cavitation cleaning of wastewater of a fatandoil plant from organic and biological contamination in the presence of various gases - Vashkurak, Uliana; Shevchuk, Liliya; Nykulyshyn, Irena; Aftanaziv, Ivan (Eastern-European Journal of Enterprise Technologies, 2018)
The use of cavitation technologies for the processes of cleaning wastewater from a fat-and-oil plant is one of the promising methods for enhancing water quality indicators. The supply of gases of different nature, such as nitrogen, oxygen, air, the mixture of nitrogen and oxygen in the ratio of 1:1, to the cavitation zone was proposed. The influence of the nature of bubbled gases both under the influence of the US and without it on the change in chemical oxygen demand and microbial number was studied. Effective constants of the rate of destruction of organic compounds and biological contaminants were calculated. It was found that the highest value of effective constant of the rate of water disinfection from MO (5.13∙10-4 s-1) was achieved at nitrogen bubbling. The highest value of water disinfection under cavitation conditions (99.9 %) was achieved in the atmosphere of nitrogen, and the highest value of degree of destruction of organic compounds of 64.3% was achieved at the simultaneous influence of the air and the US. It was determined that the process of destruction of organic contaminants and disinfection of wastewater of the fat-and-oil plant can be described by applying the kinetic equation of the first order. The relative series of influence of the nature of the studied gases on cavitation cleaning of water were established. It was shown that cleaning wastewater of the fat-and-oil plant during simultaneous bubbling of gases in the cavitation field during destruction of organic compounds is by 5–35.7 % and during water disinfection from MO by 1–90.5 % more effective than the influence of the US alone. The use of the proposed cavitation technology for cleaning wastewater of the fat-and-oil plant enables complete water disinfection from harmful MO and simultaneous destruction of organic substances. This makes it possible to eliminate the negative impact of harmful substances, contained in wastewater, for protection of the environment and the water basin of Ukraine.